EKSISTENSI OTONOMI PEMERINTAHAN DESA BERDASARKAN UNDANG-UNDANG NEGARA REPUBLIK INDONESIA NOMOR 6 TAHUN 2014 TENTANG DESA - Herlina, Herlina (Katalogis, 2017)
This writing wants to know what the legal problematics faced in implementing village autonomy based on the Law of the Republic of Indonesia Number 6 Year 2014 About the village, through the method of normative, found things as follows ; Problems of law encountered in implementing village autonomy based on the Law of the Republic of Indonesia Number 6 Year 2014 About the Village, among others; 1) The naming of indigenous villages are different so that the need for uniformity in the naming of indigenous villages; 2) In terms of the organization of village finances, oversight of the implementation of village finances are still weak, so misappropriation of village funds is still a lot going on; 3) The term of office of the village head quite long so it will give birth to